Policies of democratization of higher education in Brazil an analysis of quotas and student assistance (Research, Society and Development, 2019)
The present article is based on presenting the challenges of the democratization of higher education in Brazil related to the policies of quotas implemented through law 12.711 / 2012 and as the policies of student assistance, through Decree No. 7.234 / 2010, referring to the National Assistance Plan Students - PNAES come to collaborate with the permanence of these students in the secondary and higher education of the Federal Universities and Institutes. We noticed that the quotas policies in their implementation had several challenges. Among those who were against such policies the argument was that the academic income of these institutions would decrease and that there would be segregation of the cotitas. Among the favorable arguments would be the increase of people belonging to minority groups such as blacks, pardos and indigenous people and of different social classes, which would provide a greater acculturation of the university environment. Through qualitative exploratory research, it can be concluded that quota policies, coupled with a consistent student assistance policy, allow students not only to remain in universities and federal institutes, but also to successfully complete them. However, the challenges are great, but we realize that the two are intrinsically intertwined. From the above, we consider the association of such policies to be of fundamental importance, since in this way we could effectively enable the students to remain in the higher education environment, the conclusion, as well as the transformations expected by the affirmative actions of quotas, as an insertion social and opens the discussion about social discrimination, a subject little discussed in our society.